Reflexiones en torno al Arcaico colombiano (2015)
ABSTRACT: In the 1960s Reichel Dolmatoff applied the evolutionary model of the American archeology to order the prehispanic record in Colombia. Nonetheless, the Archaic period was loosely defined because of the lack of data existing at the time. Fifty years after that things have changed and we now have robust evidences to be able to understand this key period in the prehispanic history, characterized by its cultural diversity and the adaptive strategies plasticity displayed by the different human groups, among which the origin of food production stands out.